Multidimensional Radar Imaging - Martorella, Marco (Electromagnetics and Radar Ser., 2019)
NATO SET-196, a Research Task Group (RTG) that was active within the Sensor and Electronics Technology (SET) Panel, carried out a thorough gap analysis of imaging systems, especially when performed with single channel radar. SET-196 also explored systems and algorithms that were based on multi-channel and multi-static types of radar systems, with specific attention to their ability to outperform single channel radar in terms of imaging capabilities and performances. Research within the NATO framework is continuing along these lines with a follow-on RTG, namely SET-250, on multidimensional radar imaging. SET-250 extended the vision of SET-196 by including additional dimensions, such as multi-frequency and multi-polarisation (full-pol radar systems). Most of the results achieved within SET-196 and SET-250 are contained in this book. The Chapters in the book discuss: three-dimensional inverse synthetic aperture radar, STAP-ISAR, wide-band multi-look passive ISAR, radar tomography, multistatic PCL-SAR, sparsity-driven multistatic TSAR image reconstruction, rotor blade parameter estimation with multichannel passive radar, multistatic 3D TSAR imaging of maritime targets, semi-cooperative bi/multistatic synthetic aperture radar using Cosmo-SkyMed as an illuminator, multichannel/ multi-static radar imaging, and non-cooperative targets.